GC-MS Analysis, Bioactivity-based Molecular Networking and Antiparasitic Potential of the Antarctic Alga Desmarestia antarctica - dos Santos, Gustavo Souza; Rangel, Karen Cristina; Teixeira, Thaiz Rodrigues; Gaspar, Lorena Rigo; Abreu-Filho, Péricles Gama; Pereira, Luíz Miguel; Yatsuda, Ana Patrícia; Gallon, Marília Elias; Gobbo-Neto, Leonardo; da Costa Clementino, Leandro; Graminha, Márcia Aparecida Silva; Jordão, Laís Garcia; Pohlit, Adrian Martin; Colepicolo-Neto, Pio; Debonsi, Hosana Maria (Planta Medica International Open, 2020)
Leishmaniasis, malaria, and neosporosis are parasitic diseases that affect humans and animals, causing public health problems and billions in economic losses. Despite the advances in the development of new drugs, the severe side effects of available leishmaniasis treatments, the Plasmodium spp. resistance to antimalarial drugs, and the lack of a specific treatment against neosporosis lead us to the search for new anti-protozoan molecules from underexplored sources such as the Antarctic marine environment. Herein, we describe for the first time the chemical profile of Desmarestia antarctica crude extract and fractions using GC-MS and LC-MS/MS (molecular networking) approaches, and evaluate their antiparasitic activity against Leishmania amazonensis, Neospora caninum, and multi-drug-resistant Plasmodium falciparum. Furthermore, the cytotoxicity in 3T3 BALB/c fibroblasts and Vero cells was evaluated. D. antarctica fraction E ( IC50 of 53.8±4.4 μg mL− 1 and selectivity index of 3.3) exhibited anti-promastigote activity and was fourfold more selective to L. amazonensis rather than to the host cells. D. antarctica fraction D (IC50 of 1.6±1.3 μg mL− 1 and selectivity index of 27.8), D. antarctica fraction F (IC50 of 3.1±2.1 μg mL− 1 and selectivity index of 23.1), and D. antarctica fraction H (IC50 of 3.1±2.0 μg mL− 1 and selectivity index of 12.9) presented the highest antiparasitic effects against N. caninum with no cytotoxic effects. Also, D. antarctica fraction D presented a significant antiplasmodial inhibitory effect (IC50 of 19.1±3.9 μg mL− 1 and selectivity index of 6.0). GC-MS analysis indicated palmitic acid, myristic acid, fucosterol, phthalic acid, di(2-methylbutyl) ester, loliolide, and neophytadiene as the main components in the active fractions. In addition, this is the first report of a biological screening of macroalgae secondary metabolites against N. caninum parasites.
Keywords: desmarestiaceae; desmarestia antarctica; leishmania amazonensis; neospora caninum; plasmodium falciparum; antiparasitic; molecular targets and activities; marine macroalgae